Journeys, expeditions and itineraries across the Irish Sea: some notes from Patrick’s ‘Confessio’ and ‘Epistola’ - Santos, Dominique (Romanitas - Revista de Estudos Grecolatinos, 2022)
In Late Antiquity, communication by the Irish Sea was a fundamental factor, because. Despite some difficulties in navigation, the maritime paths were much easier than the terrestrial ones, with their mountains, bogs and the need for authorization for mobility between each location. Cultural, social and economic exchanges by sea were then frequent. Considering this, the aim of this article is to present some notes on the journeys, expeditions and itineraries in the Irish Sea taking as sources the Confessio and Epistola, two texts written by [Saint] Patrick in the 5th century.